Pengaruh Kualitas Layanan Dan Citra Perusahaan Terhadap Kepuasan Nasabah PT BANK BPD Bali Cabang Tohpati - Dewi, Kadek Martya; Agus Ariana, I Komang (LPPM Univ. Ibn Khaldun Bogor, 2021)
Currently the banking industry is experiencing increasingly fierce competition, this is evidenced by the increasing number of banks in Bali, especially in Denpasar Regency. PT Bank BPD Bali Tohpati Branch is a banking institution that provides services to customers related to its activities, namely collecting funds from the public in the form of time deposits, savings, providing credit, or other equivalent forms. With the increasing number of commercial banks each year, they also become competitors of PT Bank BPD Bali Tohpati Branch, so that currently customers have the choice to determine which bank provides higher satisfaction. Companies must continue to design a service marketing strategy that is able to meet the needs and desires of customers and has value or competitiveness with other banks. Service quality or service focuses on efforts to meet customer needs and desires, as well as the accuracy of delivery to balance customer expectations. Corporate image is the impression, feeling and image of the public towards the company, the impression that is deliberately created from an object, person or organization. Bank BPD Bali Tohpati Branch needs to maintain its customers by providing good service quality. So that customers do not seek or consider services from one bank to another, and also what is in the minds of customers, the most important example is providing comfort to customers both in terms of service.